Progress in Porcine Kidney Transplantation to Non-Human Primates - Stéphanie Le Bas-Bernardet; Gilles Blancho; Gilles Blancho (Transplant International)
Renal xenotransplantation has recently made considerable progress in overcoming the barrier to its use in humans. This progress has been made possible owing to the use of preclinical pig-to-primate models. Overall, renal xenotransplantation has long been associated with lower survival rates than that of porcine hearts (mainly due to its life-sustaining nature). However, the use of the latest strains of genetically modified porcine donors, combined with progress in the control of the anti-porcine immune response and coagulation, has now enabled survival of up to 2 years. Although the pig-to-primate combination has long been considered a perfect reflection of the human situation, it has several limitations, particularly in terms of different natural anti-porcine antibodies. This fact, in association with survival prolongation, which is considered a prerequisite, has led some pioneering teams to cross the line of human application. However, use in humans will remain anecdotal, and further progress in renal xenotransplantation will be difficult to achieve without the use of non-human primates, which will remain complementary, particularly with regard to major innovations that have never been tested in humans.